Characterization of Executive Functions and Academic Performance in Medical Students at Corporación Universitaria Remington, 2021 - Botero-Zapata, Víctor; Ospina-Uribe, Ana Carolina; Barrera, Diego Alejandro; García-Toro, Maritza; Arteaga, Aníbal; Castro-Álvarez, John Fredy (Iatreia)
Introduction: The development of executive functions, as higher-order cognitive activities, is fundamental in students' academic processes. However, results regarding their contribution to medical education are contradictory concerning short- and long-term effects. Objectives: To characterize a group of executive functions and academic performance of medical students in their second, fifth, and tenth semesters at Corporación Universitaria Remington. Methods: A descriptive cross-sectional study with a sample of 119 students from the second, fifth, and tenth semesters in 2021–2 at Corporación Universitaria Remington. A set of executive functions was characterized based on academic performance, neurocognitive tests, and sociodemographic variables. Results: Bilingual students demonstrated better scores in working memory, cognitive flexibility, and inhibitory control. Regarding the semester level, no significant correlation was obtained; however, it was observed that as students progressed through semesters, scores in working memory and inhibitory control tended to improve, while in cognitive flexibility, perseverative error scores tended to decrease. Concerning study habits, it was found that a greater number of years studied, as well as more time invested in extracurricular study, improved inhibitory control scores. Conclusions: Bilingualism was associated with better scores in executive functions. Additionally, the number of years studied and time spent on extracurricular study showed a correlation with inhibitory control.